Thermoplastic polyurethane for three‐dimensional printing applications: A review - Desai, Shubham M.; Sonawane, Rushikesh Y.; More, Aarti P. (Polymers for advanced technologies, 2023)
Additive manufacturing is an emerging technology with the advantage of less wastage, fast prototyping with customized designing suitable for a wide range of applications. Three‐dimensional (3D) printing is one of the types of additive manufacturing and various polymers are explored for 3D printing applications. Thermoplastic polyurethane (TPU) is a versatile material that has gained increasing attention in 3D printing applications due to its unique combination of mechanical, thermal, and chemical properties. This review paper provides an overview of the current state‐of‐the‐art in TPU‐based 3D printing, including its characteristics, processing techniques, and mainly its applications. Extensive studies are done in TPU with fused deposition modeling (FDM), multi‐jet fusion (MJF), and selective laser sintering (SLS). The elasticity and flexibility, layer adhesion, tensile strength, and support structure are the parameters that decide the suitability of FDM, SLS, and MJF for TPU 3D printing. The infill density, modification of processing parameters, use of sacrificial materials, addition of perforations or channels, varying the particle size, using a mixture of powders, and so forth. leads to develop the porous structure in the final product. In addition, we have studied blends of TPU with other polymers like acrylonitrile butadiene styrene (ABS) and polylactic acid (PLA), as well as fiber‐reinforced TPU composites for 3D printing applications.